Protecting Canada's natural ecosystems from invasive alien plant species: Is sub-national weed control legislation up to the task? - Lewis, Glennis M (University of Ottawa (Canada), 2006)
Invasive alien plant species pose a serious threat to Canada's natural ecosystems. It is the thesis of this paper that sub-national laws are important tools in combatting such species that are naturalized and spreading within provincial and territorial boundaries. Weed control acts in British Columbia, Alberta, Saskatchewan, Manitoba, Ontario, Quebec, Nova Scotia, and Prince Edward Island and the plant health protection acts in New Brunswick, and Newfoundland and Labrador are a strong basis to combat invasive alien plant species. However, since these laws were enacted for weeds in agro-ecosystems, they are not up to the task of protecting natural ecosystems from invasive alien plant species. In some provinces and territories, there is a need to fill gaps in the law and ensure that it applies in a clear and uniform manner to all natural ecosystems. Numerous other revisions are recommended to make applicable provincial and territorial laws more effective.
Keywords: Law.; Agriculture, Forestry and Wildlife.; Environmental Sciences.